FISHERY OF THE SWIMMING CFRAB PORTUNUS PELAGICUS LINNAEUS FROM PALK BAY AND GULF OF MANNAR - Hamsa, K M S Ameer (Indian Journal of Fisheries, 2011)
Fishery of Portunus pelagicus Linnaeus along the Palk Bay andGulf Mannar is by a type of gill net locally known as nandu valai. They are alsocaught an large numbers in trawls operated by mechanised boats. The monthlycatch pÂ«r unit effort at the three major crab fishing centres Devipattiaraam, Vedalaiand Mandapam is estimated for three years and Vedialal* is- found to be the mostproductive centre for crabs. Some information regarding the marketing, disposal,longevity of life outside seai water aid sound production are also given